(untitled) (Italian Journal of Public Health, 2004)
Dear Sir; The Section of Epidemiology and Public Health of the University “G. d’Annunzio” of Chieti, in collaboration with the Centre for Research in Medical Education and Health Care of Jefferson Medical College, Philadelphia, PA, USA, has analysed 350,000 hospital admissions for the year 2001 in the Abruzzo region. Four diseases were chosen for an in-depth analysis. These were: diabetes mellitus; cholecystitis/cholelithiasis; cancer of the female breast and bacterial pneumonia.The total admissions for these conditions were 11,000. Using the Disease Staging methodology to control for severity, a number of variables were analysed: length of hospital stay, hospital mortality, complications and repeated admissions. In addition, the timeliness of hospitalisation was analysed by grouping admissions into three categories: premature or medically unnecessary, timely, and late.An example of the first type is a patient with an elevated blood sugar but no other complications (Stage 1 Diabetes Mellitus).